2020
DOI: 10.1038/s41467-020-16840-2
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem and progenitor cell-restricted Cdx2 expression induces transformation to myelodysplasia and acute leukemia

Abstract: The caudal-related homeobox transcription factor CDX2 is expressed in leukemic cells but not during normal blood formation. Retroviral overexpression of Cdx2 induces AML in mice, however the developmental stage at which CDX2 exerts its effect is unknown. We developed a conditionally inducible Cdx2 mouse model to determine the effects of in vivo, inducible Cdx2 expression in hematopoietic stem and progenitor cells (HSPCs). Cdx2-transgenic mice develop myelodysplastic syndrome with progression to acute leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…This connection between the tumor and stromal cells is an untapped field in cancer biology. Previous studies have indicated that stem cell-derived exosomes can promote tumor progression in numerous types of tumors, thereby supporting the results of our study (30,31). Recently, researchers discovered that astrocyte-derived exosomes carrying miRNA promote brain metastasis (32) and GBM-derived exosomes transfer RNA to the microglia/macrophages in the brain (33).…”
Section: Discussionsupporting
confidence: 89%
“…This connection between the tumor and stromal cells is an untapped field in cancer biology. Previous studies have indicated that stem cell-derived exosomes can promote tumor progression in numerous types of tumors, thereby supporting the results of our study (30,31). Recently, researchers discovered that astrocyte-derived exosomes carrying miRNA promote brain metastasis (32) and GBM-derived exosomes transfer RNA to the microglia/macrophages in the brain (33).…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, this study shows that the ectopic expression of CDX2 in the hematopoietic lineage triggers acute leukemia associated with genome instability and profound changes in gene expression patterns. The malignant phenotype observed here is more drastic and penetrant than in a recent model leading predominantly to myelodysplasia by targeting CDX2 selectively in hematopoietic stem cells [10], likely because the induction of CDX2 driven by the Mx1Cre allele affects more cells of the hematopoietic lineage than only stem cells. Previous studies have shown that the proliferation of acute myeloid leukemia cells is compromised when CDX2 is knocked down, and, conversely, that inducing Cdx2 ex vivo in hematopoietic progenitors increases self‐renewal [8].…”
Section: Discussionmentioning
confidence: 63%
“…Conversely, it is ectopically turned on in precancerous metaplastic lesions of the foregut [1] and, beyond the digestive tract, in a high proportion of acute leukemia associated with poor prognosis (see Ref [7] and references therein). Cellular studies have shown that Cdx2 confers oncogenic properties to murine hematopoietic stem cells in vitro [8,9], while turning on its expression in vivo induces myelodysplastic lesions, a few of them evolving into overt leukemia [10]. However, the mechanism(s) associated with this pro-oncogenic activity remain largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, via multiple mechanisms, transcription activation can inhibit malignant cell growth. The activation of tumor suppressors can result in cell cycle arrest, [ 39,44,47,50,51 ] reactivation of endogenous retroviruses may result in blast clearance through an anti‐leukemic immune response [ 54,55 ] and finally gene expression reactivation may result in immature blast differentiation [ 39,52,53 ]…”
Section: Proposed Aza/dac Mechanism Of Action In Cancermentioning
confidence: 99%
“…[ 47 ] However, in two subsequent studies in AML [ 48 ] and CMML, [ 49 ] p15 promoter methylation did not correlate with treatment response. Other tumor suppressors like p21 [ 44,50,51 ] and p53 [ 39,44 ] were also found to be upregulated after AZA treatment. AML blasts are the result of a block of differentiation and it was postulated that gene expression reactivation may induce differentiation.…”
Section: Proposed Aza/dac Mechanism Of Action In Cancermentioning
confidence: 99%